Peran Pengasuh dalam Membentuk Karakter Religius Anak di Panti Asuhan Yayasan Gerakan Bunda Berbagi - Fitri Aswanto; Fadhilla Yusri; Sri Darma Yunita (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2024)
The role of a caregiver is very much needed by the children at the West Pasaman Mother Sharing Foundation orphanage in shaping the children's religious character. Children are educated so that they can be disciplined, responsible and able to memorize the Koran. The key informants in this research were caregivers or administrators and the supporting informants for this research were all 19 children from the orphanage. The results of this research show that there are 4 ways for caregivers to shape the character of children at the West Pasaman Mother Sharing Foundation orphanage, namely through (1). Habituation, children are accustomed to reading the Koran at 3 times, namely after the morning prayer, after the Asr prayer and after the Maghrib prayer. (2). By example, caregivers always set good examples for children to emulate, for example sunnah fasting. (3). Advice, caregivers provide advice to orphanage children who are found breaking the rules or not carrying out the tasks that have been assigned to them. And the last one (4). Punishment, caregivers give punishment to children if they have been advised but make the same mistake. So caregivers provide punishments that children can still carry out but can also have a deterrent effect on mistakes made. The research method used in this research is a qualitative research method with data collection techniques through observation, interviews and documentation.